Effect of Shear History on Rheology of Time-Dependent Colloidal Silica Gels - Paulo Santos (488565) (2017)
This paper presents a rheological study describing the effects of shear on the flow curves of colloidal gels prepared with different concentrations of fumed silica (4%, 5%, 6%, and 7%) and a hydrophobic solvent (Hydrocarbon fuel, JP-8). Viscosity measurements as a function of time were carried out at different shear rates (10, 50, 100, 500, and 1000 s−1), and based on this data, a new structural kinetics model was used to describe the system. Previous work has based the analysis of time dependent fluids on the viscosity of the intact material, i.e., before it is sheared, which is a condition very difficult to achieve when weak gels are tested. The simple action of loading the gel in the rheometer affects its structure and rheology, and the reproducibility of the measurements is thus seriously compromised. Changes in viscosity and viscoelastic properties of the sheared material are indicative of microstructural changes in the gel that need to be accounted for. Therefore, a more realistic method is presented in this work. In addition, microscopical images (Cryo-SEM) were obtained to show how the structure of the gel is affected upon application of shear. Other Information Published in: Gels License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/gels3040045